Acupuncture for headache in COVID-19: A protocol for systematic review and meta-analysis. Issue 49 (10th December 2021) - Sun, Mi; Jin, Xian; Zang, Mingxiao; Jiang, Weijia; Zhao, Chunxiao; Bi, Jieyu; Yu, Huijuan; Tan, Qiwen
Abstract: Background: Coronavirus disease 2019 (COVID-19) is an acute respiratory infectious disease which making people difficult to breathe and often accompanied with headache. Acupuncture have been proved the therapeutic effect on headache, but there has been no high-quality evidence on acupuncture for the headache in COVID-19. This study is designed to evaluate the effectiveness and safety of acupuncture for headache in COVID-19. Methods: Randomized controlled trials from December 2019 to July 2021 will be included without restrictions on language or publication date. PubMed, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Databases, China National Knowledge Infrastructure, Wanfang database, and VIP database will be searched. Two researchers will independently select studies, extract data and evaluate study quality. Cochrane risk of bias tool for randomized trials will be used to assess the risk of bias of included studies. Statistical analyses will be performed using the Review Manager V.5.3 and stata 14.0. Ethics and dissemination: This study will not involve personal information. Ethical approval will not be required. We will publish the results in a peer-reviewed journal. PROSPERO Trial registration number: CRD42021270722